Peningkatan Kapasitas Masyarakat Mol Nasi Sebagai Upaya Mengurangi Pence-maran Gas Methan (Ch4) - Nugrahini Wisnujati; Markus Patiung; Achmadi Susilo (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Natural harm is progressively disturbing the local area. This can cause sporadic seasons, streak floods in the stormy season, and constant high temperatures during the dry season. This has suggestions for individuals' lives, like diminishing food creation. Diminished food creation affects hunger. Ecological harm can be brought about by one incredibly inconsequential thing and is frequently finished by moms. That is tossing out the remainder of the food like rice. The way tossing out extra rice is quite destructive to the climate. In particular, food deterioration can affect the rise of methane gas (Ch4) contamination which is hurtful to the environment. Hence, the Agribusiness Masters, Faculty of Agriculture, Wijaya Kusuma University, Surabaya, welcomes people, particularly the PKK ladies of Customs Housing Asri Sidoarjo, to comprehend the significance of safeguarding the prevailing climate. Local area administration changed over lifeless extra rice food into neighborhood microorganisms (MOL). Since MOL can be utilized for harmless to the ecosystem, natural composts.